Péče o tunelizované žilní katétry u nemocných na domácí parenterální výživě podle současných doporučení - Víšek, J; Maňák, J; Safránek, R; Kubišová, M; Dlouhá, R; Sobotka, L; Bláha, V (Vnitrni lekarstvi, 2012)
Home parenteral nutrition is the only option to provide nutrition in a number of patients. Care of venous entry, its management and treatment of complications resulting from its use importantly affect patient survival. Appropriate care of the catheter and the use of current knowledge may prolong the lifespan of the catheter, reduce patient morbidity and mortality and thus increase quality of life of patients who are dependent on home parenteral nutrition. The present paper summarizes recommendations for the care of long-term venous catheters.
Keywords: Catheterization; Catheters, Indwelling; katetrizace; Vascular Access Devices; Parenteral Nutrition, Home; zaváděcí katétry; lidé; parenterální výživa doma; cévní přístupy; Humans